Consumer traits of common beans: a global and regional perspective on seed coat darkening, cooking time, protein, and mineral content - Mbiu, Julius; Assefa, Teshale; Mukankusi, Clare; Rubyogo, Jean Claude; Philipo, Mashamba (Frontiers in Nutrition, 2025)
Common beans (Phaseolus vulgaris L.) are a cornerstone of global nutrition, offering a sustainable source of protein, micronutrients, and bioactive compounds. This review synthesizes current research on critical consumer traits—seed coat darkening, cooking time, protein, and mineral content—highlighting their genetic, biochemical, and environmental determinants. Seed coat darkening, driven by proanthocyanidin oxidation and regulated by genes like J, sd, and Psd, significantly impacts marketability, while cooking time variations (19–271 min across genotypes) influence regional preferences and nutritional outcomes. Biofortification and low-phytic acid (lpa) breeding strategies enhance mineral bioavailability, addressing deficiencies in Sub-Saharan Africa and South Asia. Regional disparities in consumer preferences, such as the demand for fast-cooking yellow beans in East Africa, underscore the need for tailored breeding programs. Climate change poses challenges to yield and nutrient retention, necessitating climate-resilient varieties. This review proposes integrating genomics, marker-assisted selection, and postharvest innovations, for developing beans that align with consumer needs, cultural practices, and sustainability goals. This is the first synthesis linking seed coat biochemistry to regional preferences.